International relations and change: a Kuhnian interpretation - Schoeman, Jacobus (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2005)
Using notions of change developed by Thomas Kuhn, the thesis argues that the rise of globalisation and the end of the Cold War presented the Westphalian or state-centric paradigm of international relations with a Kuhnian paradigm "crisis" . As a result, both the theory and the practice of international relations are in the midst of (what Kuhn calls) a "paradigm shift" . Emerging from this shift is (what is described in this work as) "Access World" and "Denial World" "“ a particular global configuration of the practice of international relations. Kuhn's idea of "incommensurability" seems to typify the relationship between the two components of this bifurcated configuration of the international. Both intellectual risk-taking and political courage are required if the ontological struggle raging between "Access World" and "Denial World" is to be settled. This will pave the way for a new paradigm to emerge. Kuhn provides us with the insight that, to achieve this ontological breakthrough, a fundamental change in our vision of the discipline of International Relations, but also of the world of everyday international relations, is required. This entails recasting the study of International Relations as an emancipatory project and by recognising the centrality of human beings in the practice of international relations. Only if this is done, will we be able to arrive at a cosmopolitan political bargain that is appropriate for the 21st century.
Keywords: Kuhn, Thomas S; Kuhn, Thomas S -- Criticism and interpretation; International relations; International relations -- Philosophy; Knowledge, Theory of